2020
DOI: 10.1080/09638288.2020.1753830
|View full text |Cite
|
Sign up to set email alerts
|

Stroke-Specific Quality of Life one-year post-stroke in two Scandinavian country-regions with different organisation of rehabilitation services: a prospective study

Abstract: Purpose: To compare stroke-specific health related quality of life in two country-regions with organisational differences in subacute rehabilitation services, and to reveal whether organisational factors or individual factors impact outcome. Materials and methods: A prospective multicentre study with one-year follow-up of 369 first-ever stroke survivors with ischaemic or haemorrhagic stroke, recruited from stroke units in North Norway (n ¼ 208) and Central Denmark (n ¼ 161). The 12-domain Stroke-Specific Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 62 publications
(98 reference statements)
4
27
0
Order By: Relevance
“…The study demonstrated that in stroke survivors, several sociodemographic factors (being older, widow, less educated), economic factors (lower monthly family income) and clinical factors (hemorrhagic stroke type, comorbidities, high chronic mRankin score) are associated with reduced perception of QoL in different dimensions. These findings are similar to those reported in previous studies [5,6,[8][9][10][11]. A large proportion of stroke survivors have poor perception of their QoL and probably face unmet long-term needs [6].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The study demonstrated that in stroke survivors, several sociodemographic factors (being older, widow, less educated), economic factors (lower monthly family income) and clinical factors (hemorrhagic stroke type, comorbidities, high chronic mRankin score) are associated with reduced perception of QoL in different dimensions. These findings are similar to those reported in previous studies [5,6,[8][9][10][11]. A large proportion of stroke survivors have poor perception of their QoL and probably face unmet long-term needs [6].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to those reported in previous studies [5,6,[8][9][10][11]. A large proportion of stroke survivors have poor perception of their QoL and probably face unmet long-term needs [6]. Sociodemographic, economic and health factors have been shown to influence the QoL of stroke survivors [18][19][20].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Impact of general mobility, motor dysfunction and social interactions on the QOL have been reported in recent researches [18,24], though they have not focused precisely on different parameters of post-stroke motor dysfunction, i.e. upper extremity function.…”
Section: Resultsmentioning
confidence: 99%